O Direito Eleitoral no Brasil: análise crítica e alternativas para seu aprimoramento - Silveira, Raquel Coelho Dal Rio (2018)
The present paper begins with the concept of law, politics, democracy and ethics and the relation between them. It does a critical analysis of some institutes of the Electoral Law, aiming to demonstrate how the model of financing of electoral campaign in Brazil interferes in the governability and governance of the country, generating corruption, crisis of representativeness and, ultimately, compromising the implementation of public policies and the democratic ideal. Also, in spite of the constitutional prediction of political parties pluralism, proves that the existence of excessive number of parties and the lack of intra-party democracy, as it happens today, has been harmful. The Electoral Court, for its part, in the way it is structured, also deserves criticism. Considering the Court’s federal nature, its jurisdiction must be exercised by federal judges. Finally, some suggestions are made, to improve the Electoral Law in Brazil